Early Marriage According to the Views of Muhammadiyah Figures and Nahdlatul Ulama Leaders (Case Study in Fisherman Village Communities, Medan Marelan District) - Desi Handayani Daulay; Amal Hayati; Rahmad Efendi (JURNAL HUKUM SEHASEN, 2023)
In this modern era, early marriage still occurs in many regions and regions in Indonesia. For example, a phenomenon that occurs in one of the villages in the city of Medan, namely in Labuhan Village or Fisherman's Village, Medan Marelan District. Many teenagers who do early marriage in the Fisherman Village, Medan Marelan District. Between the ages of 15-17 years, the time span is from August 2021 to January 2022. There are 5-10 teenagers who do early marriages that occur in the Fisherman Village, Medan Marelan District. From the description above, the researcher is interested in discussing the thesis with the title "Early Marriage According to the View of Muhammadiyah Figures and Nahdlatul Ulama Figures (Case Study in the Fisherman Village Community, Medan Marelan District). The problem raised in this study is how Early Marriage According to the View of Muhammadiyah and Nahdlatul Ulama figures, Medan Marelan District, as for the right method to achieve maximum results in this research, namely the Sociological Empirical research method which is comparative. This research is a field research based on research reports. The type of research used in this research is qualitative research. The research subject in this study is a special review of the opinions of Muhammadiyah figures and Nahdlatul Ulama figures in Medan Marelan District. In this study, the author tries to collect the opinions of Muhammadiyah figures and Nahdlatul Ulama figures, then analyzes the opinions of these two mass organizations, and the results of the collection of opinions, namely, Muhammadiyah leaders are that they are more likely to agree with Law no. 16 of 2019 Regarding Marriage, Muhammadiyah Leaders assess this for the common good, because of what the government has made for the good of its people, and the Opinions of Nahdlatul Ulama Figures Some of them are of the opinion that the marriage of the Prophet SAW and Aisyah and made the Hadith of Aisyah as legal basis for allowing underage marriage. Based on the descriptions that the researchers have done, it can be concluded that the opinions of Muhammadiyah figures are more relevant because the government regulations, namely Law no. 16 of 2019 concerning the limitation of the age for marriage, this is considered mature enough in marriage so as to reduce the divorce rate due to early marriage in fishing village communities, and in this case the government also makes regulations for the benefit of the community.